Analysis of Determinants of Stock Returns in Transportation Sub-Sector Companies on the IDX - Astarina, Yesita; Nurcahaya , Claudya; Riana, Dwi (Graduate Program Magister Manajemen Pendidikan, 2025)
This study aims to determine whether financial risk and business risk can affect stock returns in transportation companies listed on the Indonesia Stock Exchange. This study is an associative study with a quantitative approach. The population in this study is all transportation companies listed on the IDX during the period 2019-2023. The sampling technique used the purposive sampling method with the number of samples obtained being 10 companies. This study uses secondary data and data analysis techniques using multiple linear regression analysis with SmartPLS program, and hypothesis testing using partial t-tests. The results of this research show that based on partial tests, financial risk and business risk do not have a significant effect on stock returns. The coefficient of determination value obtained was 3.2%, meaning that there are other variables that contribute to stock returns which were not examined in this research.